Composite oxide carrier, supported catalyst, hydrogenated butadiene-acrylonitrile rubber and preparation method and application thereof

By using a supported catalyst prepared by using a composite oxide support and non-precious metal active component, combined with the coordinated coordination of homogeneous catalysts, the problems of catalyst separation difficulties and precious metal residues are solved, and the efficient hydrogenation process of nitrile rubber is achieved, reducing the temperature and temperature of the hydrogenated nitrile rubber. Production costs and improve product quality.

CN119425654AActive Publication Date: 2025-02-14CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311575639.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-03
Filing Date
2023-11-23
Publication Date
2025-02-14
Estimated Expiration
2043-11-23

AI Technical Summary

Technical Problem

In the hydrogenation process of hydrogenated nitrile rubber, there are problems such as difficulty in separating the catalyst from the product, residues of precious metals lead to high production costs and accelerated product aging rate.

Method used

Using composite oxide support, the dispersion of the active components of the catalyst is improved through surface treatment, and non-precious metals are used as active components to prepare a supported catalyst with small particle size, and cooperate with the homogeneous catalyst to achieve efficient hydrogenation reaction. .

Benefits of technology

The hydrogenation activity and reusability of the catalyst are improved, production costs are reduced, and the degree and stability of the product are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119425654A_ABST
    Figure CN119425654A_ABST
Patent Text Reader

Abstract

The invention discloses a composite oxide carrier, a supported catalyst, hydrogenated butadiene-acrylonitrile rubber and a preparation method and application thereof. The composite oxide carrier comprises SiO2 and IVB group metal oxide, the IVB group metal oxide is TiO2 and / or ZrO2, and the surface characteristic of the composite oxide carrier is that three characteristic peaks exist at 610-720 cm <-1 > and three characteristic peaks exist at 2840-2970 cm <-1 > in an infrared spectrum. The composite oxide carrier can significantly improve the dispersion of active components on the surface of the catalyst and significantly improve the hydrogenation activity of the catalyst. According to the present invention, the supported catalyst and the homogeneous catalyst cooperate, the high-molecular polymer material is subjected to hydrogenation saturation at the low temperature and the low pressure, and the prepared high-molecular polymer (especially the hydrogenated butadiene-acrylonitrile rubber) product has the high hydrogenation degree; and the supported catalyst can be repeatedly used, so that the recoverability of the catalyst is improved, and the preparation cost is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite oxide carrier and a preparation method thereof, a supported catalyst and a preparation method thereof, and hydrogenated nitrile rubber and a preparation method and application thereof. Background Art

[0002] Nitrile rubber (NBR) is a copolymer made of acrylonitrile and butadiene monomers. It has excellent oil resistance, high wear resistance, good heat resistance and strong adhesion. Its disadvantages are poor low temperature resistance, poor odor resistance, low insulation performance and low elasticity. It is widely used in the preparation of various oil-resistant rubber products in the fields of automobiles, aviation, petroleum, etc.

[0003] Hydrogenated nitrile rubber (HNBR) is a product produced by catalytic selective hydrogenation of unsaturated olefin segments on the hydrocarbon chain of nitrile rubber (NBR). Hydrogenated nitrile rubber has excellent characteristics such as good oil resistance, heat resistance, chemical corrosion resistance, odor resistance, high tear resistance and wear resistance.

[0004] At present, the main method for industrial production of HNBR is solution hydrogenation, and solution hydrogenation mainly includes homogeneous hydrogenation and heterogeneous hydrogenation. Homogeneous hydrogenation refers to the process in which the active components of the catalyst are dispersed in the polymer solution in molecular form, and the polymer is subjected to catalytic hydrogenation under certain reaction conditions. The reactants and catalysts of the homogeneous hydrogenation reaction are evenly mixed, the reaction conditions are easy to control, and the output product has stable performance. However, a common disadvantage of the homogeneous solution hydrogenation method is that it is difficult to separate the catalyst from the product. Although a variety of technologies have been developed, such as ion exchange of precious metals using ion exchange resins, aqueous extraction and recovery of precious metal rhodium using the complexation of stannous chloride and rhodium catalysts, and temperature-controlled phase transfer catalysts, these methods are difficult to completely remove the remaining precious metal catalysts in the polymer or may produce gels that affect product quality, and the cost of large-scale industrialization is extremely high. The residue of precious metals in the hydrogenation product will increase production costs and waste precious metal resources on the one hand; on the other hand, it will accelerate the aging rate of HNBR and affect the mechanical processing properties of the polymer.

[0005] Compared with the homogeneous hydrogenation catalytic system, the heterogeneous catalytic reaction system uses a supported precious metal catalyst, which can well solve the problem of separation of catalyst and hydrogenation product, not only making it possible to reuse the precious metal catalyst, but also effectively avoiding the residue of precious metal in the polymer. At present, the preparation of supported catalyst still relies on the traditional impregnation method, which leads to a larger particle size of the active component, significantly reducing the number of active centers, and because the interaction between the active component and the carrier is weak, it is easy to cause the precious metal to detach and lose from the surface of the carrier after strong stirring reaction, which reduces the availability of the catalyst and affects the performance of the hydrogenation product. Ruiong Company uses SiO2 as a carrier to load Pd metal for hydrogenation preparation of nitrile rubber. The hydrogenation degree is above 95% at one time, but the effect of multiple uses of the catalyst is poor. For example, the activity begins to decrease after the second use, and the activity decreases significantly after the 3rd-4th use, and the degree of hydrogenation decreases significantly.

[0006] The use of homogeneous catalytic hydrogenation method has a high degree of hydrogenation, but the catalyst separation is difficult and the cost is increasing. The use of heterogeneous catalyst hydrogenation method to saturate high molecular polymers has an insufficient degree of hydrogenation, and there is a phenomenon of loss of active components during the stirring process of the reactor or the effect of repeated use of the catalyst is poor, and the degree of hydrogenation is significantly reduced. Therefore, it is necessary to develop a catalyst and related use methods that can ensure a high degree of hydrogenation, easy separation and recovery of the catalyst, and multiple use of the heterogeneous catalyst.

[0007] The above catalysts currently all use precious metals such as rhodium, palladium, ruthenium, osmium, platinum, and iridium as active components. The prior art has not yet disclosed a supported heterogeneous nitrile rubber supported catalyst with high activity, high selectivity, and high stability using non-precious metals as active components. Summary of the invention

[0008] In view of the above problems existing in the prior art, the present invention provides a novel composite oxide carrier, the surface characteristics of which are as follows: -1 There are three characteristic peaks at 2840-2970cm -1There are three characteristic peaks at the place, which can significantly improve the dispersion of the active components on the catalyst surface, and the control active component atomic cluster is not more than 5nm, thereby significantly improving the hydrogenation activity of the catalyst. And the novel multifunctional supported non-precious metal supported catalyst of the present invention, with SiO2 microspheres as carrier, non-precious metals as the main active components, and the particle size is relatively small. The method of adopting and coordinating with homogeneous catalysts is ensured to saturate the high molecular polymer material hydrogenation at a relatively low temperature and pressure, and the obtained hydrogenated high molecular polymer (for example hydrogenated nitrile butadiene rubber) product has a higher degree of hydrogenation. And the supported catalyst of the present invention can be repeatedly used, and the catalyst composition is easily separated and recovered. More meaningfully, non-precious metals have been used to prepare supported catalysts for active components, avoiding the problem of the loss of precious metal active components, further improving the recyclability of the catalyst, significantly reducing the cost of the catalyst, thereby reducing the production cost of hydrogenated high molecular polymer (for example hydrogenated nitrile butadiene rubber).

[0009] The first aspect of the present invention provides a composite oxide carrier, characterized in that it comprises: SiO2 and a Group IVB metal oxide, wherein the Group IVB metal oxide is TiO2 and / or ZrO2, and the surface characteristics of the composite oxide carrier are infrared spectra at 610-720cm -1 There are three characteristic peaks at 2840-2970cm -1 In the present invention, the infrared spectrum measurement conditions are: using a nicolet iS50 infrared spectrometer, sample preparation and scanning using attenuated total reflection mode, scanning range: 4000 ~ 400cm -1 , resolution 4cm -1 , scan times 32 times. For example Figure 1 As shown, the surface characteristics of the composite oxide carrier of the present invention are as follows: -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks.

[0010] According to some embodiments of the composite oxide support of the present invention, the surface characteristics of the composite oxide support are as follows: -1 There are three characteristic peaks at 2850-2960cm -1 There are three characteristic peaks.

[0011] According to some embodiments of the composite oxide support of the present invention, the surface characteristics of the composite oxide support are as follows: -1 、649±1cm -1 、708±1cm -1There is a characteristic peak at 2850±1cm; and / or, the surface characteristic of the composite oxide support is that the infrared spectrum is -1 、2919±1cm -1 、2955±1cm -1 There are characteristic peaks.

[0012] According to some embodiments of the composite oxide support of the present invention, the composite oxide support is obtained by surface treating a composite oxide support precursor of SiO2 and Group IVB metal oxide with an impregnation solution containing an organic cationic quaternary ammonium salt.

[0013] According to some embodiments of the composite oxide support of the present invention, the organic cationic quaternary ammonium salt is a C6 or higher long-chain alkyl quaternary ammonium salt, more preferably a C6 or higher long-chain alkyl halogen quaternary ammonium salt. More preferably, the halogen is Cl, Br or I, more preferably Cl. More preferably, the C6 or higher long-chain alkyl is C6-C 24 Alkyl, more preferably C8-C 22 Alkyl, more preferably C 10 -C 20 Alkyl, more preferably C 12 -C 18 More preferably, the organic cationic quaternary ammonium salt is selected from dimethyl dioctadecyl ammonium chloride, hexadecyl trimethyl ammonium chloride and C 12-14 -At least one of alkyl dimethyl ethyl benzyl ammonium chloride.

[0014] According to some embodiments of the composite oxide support of the present invention, the surface treatment is impregnation and drying. That is, in the whole process of surface treatment of the composite oxide support precursor using the organic cationic quaternary ammonium salt, no high temperature (e.g., above 300°C) treatment steps such as roasting, calcining or sintering are included. In the infrared spectrum of the composite oxide support according to the present invention, in the range of 610-720cm -1 Three characteristic peaks at 620-710 cm -1 Three characteristic peaks at 620±1cm -1 、649±1cm -1 、708±1cm -1 The characteristic peaks at 2840-2970cm -1 Three characteristic peaks at 2850-2960cm -1 Three characteristic peaks at 2850±1cm -1 、2919±1cm -1 、2955±1cm -1 The characteristic peak at is mainly attributed to CH vibration.

[0015] According to some embodiments of the method for preparing the composite oxide support of the present invention, based on the total weight of the composite oxide support, the content of the Group IVB metal oxide is 5 to 25 wt %, and the content of SiO 2 is 75 to 95 wt %. For example, but not limited to, the content of the Group IVB metal oxide is 5-20wt%, 5-15wt%, 5-10wt%, 10-25wt%, 10-20wt%, 10-15wt%, 12-25wt%, 12-20wt%, 12-15wt%, 15-25wt%, 15-20wt%, 20-25wt%, etc., and correspondingly, the content of SiO2 is 80-95wt%, 85-95wt%, 90-95wt%, 75-90wt%, 80-90wt%, 85-90wt%, 75-88wt%, 80-88wt%, 85-88wt%, 75-85wt%, 80-85wt%, 75-80wt%, etc. Preferably, the content of the Group IVB metal oxide is 10-25wt%, and the content of SiO2 is 75-90wt%. Preferably, the content of Group IVB metal oxide is greater than 10-25wt%, and the content of SiO2 is 75-less than 90wt%. Preferably, the content of Group IVB metal oxide is 11-25wt%, and the content of SiO2 is 75-89wt%. Preferably, the content of Group IVB metal oxide is 12-25wt%, and the content of SiO2 is 75-88wt%. Preferably, the content of Group IVB metal oxide is 15-25wt%, and the content of SiO2 is 75-85wt%.

[0016] According to some embodiments of the method for preparing a composite oxide support of the present invention, if the Group IVB metal oxide is TiO2 and ZrO2, the ratio of TiO2 to ZrO2 can vary within a wide range, for example but not limited to, the weight ratio of TiO2 to ZrO2 is 0.01-100:1, 0.05-20:1, 0.1-10:1, 0.3-3:1, 0.5-2:1, 1-100:1, 1-20:1, 1-10:1, 1-3:1, 1-2:1, 0.01-1:1, 0.05-1:1, 0.1-1:1, 0.3-1:1, 0.5-1:1.

[0017] According to some embodiments of the preparation method of the composite oxide carrier of the present invention, the particle size of the composite oxide carrier is 5 to 30 μm. For example, but not limited to 5 to 25 μm, 5 to 20 μm, 5 to 15 μm, 5 to 10 μm, 10 to 30 μm, 10 to 25 μm, 10 to 20 μm, 10 to 15 μm, 15 to 30 μm, 15 to 25 μm, 15 to 20 μm, 20 to 30 μm, 20 to 25 μm, etc., including the range between any two values ​​​​above. In the present invention, the particle size of the composite oxide carrier is measured according to the NB / SH / T0951-2017 test method, using a laser particle size analyzer of the MS2000 model produced by Malvern.

[0018] According to some embodiments of the preparation method of the composite oxide support of the present invention, the average pore size of the composite oxide support is 100-1200nm. For example, but not limited to, 100-1000nm, 100-800nm, 100-600nm, 100-500nm, 100-400nm, 100-300nm, 100-200nm, 200-1200nm, 200-1000nm, 200-800nm, 200-600nm, 200-500nm, 200-400nm, 200-300nm, 300-1200nm, 300-1000nm, 300-800nm, 300-600nm, 300-500nm, 300-400nm, 400-1200nm, 400 ~1000nm, 400~800nm, 400~600nm, 400~500nm, 500~1200nm, 500~1000nm, 500~800nm, 500~600nm, 600~1200nm, 600~1000nm, 600~800nm, 600~700nm, 700~1200nm, 700~1000nm, 700~800nm, 800~1200nm, 800~1000nm, 900~1200nm, 900~1000nm, 1000~1200nm, etc., including ranges between any two of the above values. In the present invention, the average pore size of the composite oxide carrier is measured according to the first part of the mercury intrusion method for determining the pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method in GBT 21650.1-2008, using the high-performance fully automatic mercury intrusion instrument AutoPoreIV 9500 of Micromeritics Instruments, USA.

[0019] According to some embodiments of the method for preparing the composite oxide carrier of the present invention, the specific surface area of ​​the composite oxide carrier is 30-200 m 2 / g. For example, but not limited to 30 to 150 m2 / g, 30~120m 2 / g, 30~100m 2 / g, 30~90m 2 / g, 30~80m 2 / g, 30~70m 2 / g, 30~60m 2 / g, 30~50m 2 / g, 30~40m 2 / g, 50~200m 2 / g, 50~150m 2 / g, 50~120m 2 / g, 50~100m 2 / g, 50~90m 2 / g, 50~80m 2 / g, 50~70m 2 / g, 50~60m 2 / g, 80~200m 2 / g, 80~150m 2 / g, 80~120m 2 / g, 80~100m 2 / g, 80~90m 2 / g, 100~200m 2 / g, 100~150m 2 / g, 100~120m 2 / g, 120~200m 2 / g, 120~150m 2 / g, etc., including the range between any two values ​​mentioned above. In the present invention, the specific surface area of ​​the composite oxide carrier is measured according to the first part of the mercury intrusion method for determining the pore size distribution and porosity of solid materials by mercury intrusion method and gas adsorption method in GBT 21650.1-2008, and is measured by using a high-performance fully automatic mercury intrusion instrument of the AutoPoreIV 9500 model of Micromeritics Instruments, USA.

[0020] The second aspect of the present invention provides a method for preparing the above-mentioned composite oxide carrier, comprising the following steps:

[0021] (1) first impregnating a SiO2 microsphere carrier with a solution containing a Group IVB metal compound, then first drying and first calcining to obtain an oxide composite carrier precursor, wherein the Group IVB metal compound is a titanium-containing compound and / or a zirconium-containing compound;

[0022] (2) The composite oxide support precursor is surface treated with an impregnation solution containing an organic cationic quaternary ammonium salt to obtain the composite oxide support.

[0023] According to some embodiments of the method for preparing a composite oxide support of the present invention, the impregnation solution containing an organic cationic quaternary ammonium salt comprises an organic cationic quaternary ammonium salt, a solvent, and an acid.

[0024] According to some embodiments of the method for preparing the composite oxide support of the present invention, the organic cationic quaternary ammonium salt is a C6 or higher long-chain alkyl quaternary ammonium salt, more preferably a C6 or higher long-chain alkyl halogen quaternary ammonium salt. More preferably, the halogen is Cl, Br or I, more preferably Cl. More preferably, the C6 or higher long-chain alkyl is C6-C 24 Alkyl, more preferably C8-C 22 Alkyl, more preferably C 10 -C 20 Alkyl, more preferably C 12 -C 18 More preferably, the organic cationic quaternary ammonium salt is selected from dimethyl dioctadecyl ammonium chloride, hexadecyl trimethyl ammonium chloride and C 12-14 -At least one of alkyl dimethyl ethyl benzyl ammonium chloride.

[0025] According to some embodiments of the method for preparing the composite oxide support of the present invention, the solvent is selected from at least one of deionized water, methanol, ethanol, acetone, butanone, tetrahydrofuran, o-xylene, p-xylene and pyridine. Preferably, the solvent is selected from at least one of o-xylene, p-xylene and pyridine. More preferably, the solvent is o-xylene or pyridine.

[0026] According to some embodiments of the method for preparing the composite oxide support of the present invention, the acid is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid and citric acid. Preferably, the acid is hydrochloric acid. More preferably, the concentration of the acid is 1 to 98.3 wt%.

[0027] According to some embodiments of the method for preparing the composite oxide support of the present invention, in the impregnation solution containing the organic cationic quaternary ammonium salt, the concentration of the quaternary ammonium salt solution is 0.1 to 10 wt %. More preferably, the weight ratio of the organic cationic quaternary ammonium salt, the solvent, and the acid is 1:10 to 19:1 to 3. For example, 1 mL of 37 wt % concentrated hydrochloric acid in the embodiment weighs 1.18 g.

[0028] According to some embodiments of the preparation method of the composite oxide support of the present invention, the surface treatment is impregnation and drying. Preferably, the conditions of the impregnation include: a temperature of 20 to 60°C and a time of 0.5 to 8 hours; the conditions of the drying include: a temperature of 50 to 120°C and a time of 2 to 10 hours. In the entire process of surface treatment of the composite oxide support precursor using an organic cationic quaternary ammonium salt, no high temperature (e.g., above 300°C) treatment steps such as roasting, calcining or sintering are included. Thus, the organic cationic quaternary ammonium salt and the acid groups (such as amino, hydrogen ion, halide ion, alkyl, etc.) can be retained on the composite oxide support, and these groups can interact with the active components, thereby promoting the dispersion of the active components.

[0029] In the present invention, the SiO2 microsphere carrier can be simultaneously impregnated with a solution of a titanium compound and / or a zirconium compound, and then dried and calcined to obtain a composite oxide carrier of SiO2, TiO2 and / or ZrO2; the SiO2 microsphere carrier can also be first impregnated with a solution of a titanium compound, and then dried and calcined, and then impregnated with a solution of a zirconium compound, and then dried and calcined to obtain a composite oxide carrier of SiO2, TiO2 and / or ZrO2; the SiO2 microsphere carrier can also be first impregnated with a solution of a zirconium compound, and then dried and calcined, and then impregnated with a solution of a titanium compound, and then dried and calcined to obtain a composite oxide carrier of SiO2, TiO2 and / or ZrO2.

[0030] According to some embodiments of the preparation method of the composite oxide carrier of the present invention, the particle size of the SiO2 microsphere carrier is 5 to 30 μm. For example, but not limited to 5 to 25 μm, 5 to 20 μm, 5 to 15 μm, 5 to 10 μm, 10 to 30 μm, 10 to 25 μm, 10 to 20 μm, 10 to 15 μm, 15 to 30 μm, 15 to 25 μm, 15 to 20 μm, 20 to 30 μm, 20 to 25 μm, etc., including the range between any two values ​​​​above. In the present invention, the particle size of the SiO2 microsphere carrier is measured according to the NB / SH / T 0951-2017 test method, using a laser particle size analyzer of the MS2000 model produced by Malvern.

[0031] According to some embodiments of the preparation method of the composite oxide carrier of the present invention, the average pore size of the SiO2 microsphere carrier is 100-1200nm. For example, but not limited to, 100-1000nm, 100-800nm, 100-600nm, 100-500nm, 100-400nm, 100-300nm, 100-200nm, 200-1200nm, 200-1000nm, 200-800nm, 200-600nm, 200-500nm, 200-400nm, 200-300nm, 300-1200nm, 300-1000nm, 300-800nm, 300-600nm, 300-500nm, 300-400nm, 400-1200nm, 400 ~1000nm, 400~800nm, 400~600nm, 400~500nm, 500~1200nm, 500~1000nm, 500~800nm, 500~600nm, 600~1200nm, 600~1000nm, 600~800nm, 600~700nm, 700~1200nm, 700~1000nm, 700~800nm, 800~1200nm, 800~1000nm, 900~1200nm, 900~1000nm, 1000~1200nm, etc., including ranges between any two of the above values. In the present invention, the average pore size of the SiO2 microsphere carrier is measured according to the first part of the mercury intrusion method for determining the pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method in GBT 21650.1-2008, using the high-performance fully automatic mercury intrusion instrument AutoPoreIV 9500 of Micromeritics Instruments, USA.

[0032] According to some embodiments of the method for preparing the composite oxide carrier of the present invention, the specific surface area of ​​the SiO2 microsphere carrier is 30-200m 2 / g. For example, but not limited to 30 to 150 m 2 / g, 30~120m 2 / g, 30~100m 2 / g, 30~90m 2 / g, 30~80m 2 / g, 30~70m 2 / g, 30~60m 2 / g, 30~50m 2 / g, 30~40m 2 / g, 50~200m 2 / g, 50~150m 2 / g, 50~120m 2 / g, 50~100m2 / g, 50~90m 2 / g, 50~80m 2 / g, 50~70m 2 / g, 50~60m 2 / g, 80~200m 2 / g, 80~150m 2 / g, 80~120m 2 / g, 80~100m 2 / g, 80~90m 2 / g, 100~200m 2 / g, 100~150m 2 / g, 100~120m 2 / g, 120~200m 2 / g, 120~150m 2 / g, etc., including the range between any two values ​​mentioned above. In the present invention, the specific surface area of ​​the SiO2 microsphere carrier is measured according to the first part of the mercury intrusion method for determining the pore size distribution and porosity of solid materials by mercury intrusion method and gas adsorption method in GBT 21650.1-2008, and is measured by using the high-performance fully automatic mercury intrusion instrument of AutoPoreIV 9500 model of Micromeritics Instruments, USA.

[0033] According to some embodiments of the method for preparing the composite oxide carrier of the present invention, the surface characteristics of the composite oxide after the quaternary ammonium salt treatment are as follows: -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks at the infrared spectra. The infrared spectra can be measured by using a nicolet iS50 infrared spectrometer. The sample preparation and scanning adopt the attenuated total reflection mode. The scanning range is 4000~400cm -1 , resolution 4cm -1 , scan times 32 times.

[0034] In the present invention, the silica microsphere carrier can be purchased commercially (for example, from Shandong Bangkai Materials Co., Ltd., Beijing Bailingwei Technology Co., Ltd., Shanghai Aladdin Biochemical Technology Co., Ltd., etc.) or homemade.

[0035] According to some embodiments of the method for preparing the composite oxide support of the present invention, the titanium-containing compound is selected from at least one of titanium sulfate, metatitanic acid, titanium tetrachloride and tetrabutyl titanate. For example, titanium sulfate or titanium tetrachloride can be dissolved in water. For another example, metatitanic acid can be dissolved in a dilute sulfuric acid solution. For another example, tetrabutyl titanate can be dissolved in an ethanol solution.

[0036] According to some embodiments of the method for preparing the composite oxide support of the present invention, the zirconium-containing compound is selected from at least one of zirconium tetrachloride, zirconium sulfate, zirconium nitrate, zirconium oxychloride and zirconium oxalate. For example, the above zirconium compound can be dissolved in water.

[0037] According to some embodiments of the method for preparing the composite oxide support of the present invention, in the solution containing titanium compound and / or zirconium compound, the concentration of titanium compound and / or zirconium compound is 0.1-1.0 mol / L, such as but not limited to 0.1-0.8 mol / L, 0.1-0.6 mol / L, 0.1-0.4 mol / L, 0.2-1.0 mol / L, 0.2-0.8 mol / L, 0.2-0.6 mol / L, 0.2-0.4 mol / L, 0.3-1.0 mol / L, 0.3-0.8 mol / L, 0.3-0.6 mol / L, 0.3-0.4 mol / L, 0.4-1.0 mol / L, 0.4-0.8 mol / L, 0.4-0.6 mol / L, 0.5-1.0 mol / L, 0.5-0.8 mol / L, 0.5-0.6 mol / L, etc., including the range between any two values ​​mentioned above.

[0038] According to some embodiments of the method for preparing the composite oxide carrier of the present invention, the molar ratio of the SiO2 microsphere carrier to the Group IVB metal compound is 3 to 40:1, for example, 4 to 26:1, 5 to 30:1, 6 to 39:1, wherein the molar amount of the SiO2 microsphere carrier is calculated based on Si, and the amount of the titanium-containing compound and / or the zirconium-containing compound is calculated based on titanium and / or zirconium elements.

[0039] According to some embodiments of the method for preparing a composite oxide support of the present invention, the conditions for the first impregnation include: a temperature of 20 to 60° C. and a time of 0.5 to 8 h.

[0040] According to some embodiments of the method for preparing a composite oxide support of the present invention, the first drying conditions include: a temperature of 105 to 130° C. and a time of 2 to 8 hours.

[0041] According to some embodiments of the method for preparing a composite oxide support of the present invention, the conditions for the first calcination include: a temperature of 450 to 650° C. and a time of 3 to 8 hours.

[0042] The third aspect of the present invention provides a supported catalyst, comprising: the above-mentioned composite oxide carrier, and active components Cu and its oxides supported on the carrier; the atomic cluster particle size of the active component copper is not greater than 5nm; based on the total weight of the supported catalyst, the content of Cu and its oxides calculated as CuO is 5-25wt%, preferably 8-25wt%, preferably 10-25wt%, preferably 12-25wt%.

[0043] According to some embodiments of the supported catalyst of the present invention, the particle size of the supported catalyst is 5 to 30 μm. For example, but not limited to 5 to 25 μm, 5 to 20 μm, 5 to 15 μm, 5 to 10 μm, 10 to 30 μm, 10 to 25 μm, 10 to 20 μm, 10 to 15 μm, 15 to 30 μm, 15 to 25 μm, 15 to 20 μm, 20 to 30 μm, 20 to 25 μm, etc., including the range between any two values ​​​​above. In the present invention, the particle size of the catalyst is measured according to the NB / SH / T0951-2017 test method, using a laser particle size analyzer of the MS2000 model produced by Malvern Company.

[0044] According to some embodiments of the supported catalyst of the present invention, the average pore size of the supported catalyst is 100-1200 nm. For example, but not limited to, 100-1000 nm, 100-800 nm, 100-600 nm, 100-500 nm, 100-400 nm, 100-300 nm, 100-200 nm, 200-1200 nm, 200-1000 nm, 200-800 nm, 200-600 nm, 200-500 nm, 200-400 nm, 200-300 nm, 300-1200 nm, 300-1000 nm, 300-800 nm, 300-600 nm, 300-500 nm, 300-400 nm, 400-1200 nm, 400 ~1000nm, 400~800nm, 400~600nm, 400~500nm, 500~1200nm, 500~1000nm, 500~800nm, 500~600nm, 600~1200nm, 600~1000nm, 600~800nm, 600~700nm, 700~1200nm, 700~1000nm, 700~800nm, 800~1200nm, 800~1000nm, 900~1200nm, 900~1000nm, 1000~1200nm, etc., including ranges between any two of the above values. In the present invention, the average pore size of the catalyst is measured according to the first part of the mercury intrusion method for determining the pore size distribution and porosity of solid materials by mercury intrusion and gas adsorption method in GBT 21650.1-2008, using the AutoPoreIV 9500 high-performance fully automatic mercury intrusion instrument of Micromeritics Instruments, USA.

[0045] According to some embodiments of the supported catalyst of the present invention, the specific surface area of ​​the supported catalyst is 30 to 200 m 2 / g. For example, but not limited to 30 to 150 m 2 / g, 30~120m 2 / g, 30~100m 2 / g, 30~90m 2 / g, 30~80m 2 / g, 30~70m 2 / g, 30~60m 2 / g, 30~50m 2 / g, 30~40m 2 / g, 50~200m 2 / g, 50~150m 2 / g, 50~120m 2 / g, 50~100m 2 / g, 50~90m2 / g, 50~80m 2 / g, 50~70m 2 / g, 50~60m 2 / g, 80~200m 2 / g, 80~150m 2 / g, 80~120m 2 / g, 80~100m 2 / g, 80~90m 2 / g, 100~200m 2 / g, 100~150m 2 / g, 100~120m 2 / g, 120~200m 2 / g, 120~150m 2 / g, etc., including the range between any two values ​​mentioned above. In the present invention, the specific surface area of ​​the catalyst is measured according to the first part of the mercury intrusion method for determining the pore size distribution and porosity of solid materials by mercury intrusion method and gas adsorption method in GBT 21650.1-2008, and is measured using a high-performance fully automatic mercury intrusion instrument of the AutoPoreIV 9500 model from Micromeritics Instruments, USA.

[0046] According to some embodiments of the supported catalyst of the present invention, the atomic cluster particle size of the active component copper is 2 to 5 nm. The determination method is characterized by transmission electron microscopy (TEM) and measured according to the scale.

[0047] According to some embodiments of the supported catalyst of the present invention, the supported catalyst is substantially free of precious metals such as rhodium, palladium, ruthenium, osmium, platinum, iridium, etc. The wording "substantially free" means that the content of precious metals such as rhodium, palladium, ruthenium, osmium, platinum, iridium, etc. in the supported catalyst is less than 1wt%, preferably less than 0.5wt%, preferably less than 0.2wt%, preferably less than 0.1wt%, preferably 0%. Preferably, the supported catalyst is completely free of precious metals such as rhodium, palladium, ruthenium, osmium, platinum, iridium, etc.

[0048] According to some embodiments of the supported catalyst of the present invention, the supported catalyst is substantially free of non-precious metals such as cobalt, nickel, molybdenum, zinc, iron, etc. except copper, titanium and zirconium. The wording "substantially free" means that the content of non-precious metals such as cobalt, nickel, molybdenum, zinc, iron, etc. except copper, titanium and zirconium in the supported catalyst is less than 1wt%, preferably less than 0.5wt%, preferably less than 0.2wt%, preferably less than 0.1wt%, preferably 0%. Preferably, the supported catalyst is completely free of non-precious metals such as cobalt, nickel, molybdenum, zinc, iron, etc. except copper, titanium and zirconium.

[0049] According to some embodiments of the supported catalyst of the present invention, the supported catalyst is substantially free of metals other than copper, titanium and zirconium. The wording "substantially free" means that the content of metals other than copper, titanium and zirconium in the supported catalyst is less than 1wt%, preferably less than 0.5wt%, preferably less than 0.2wt%, preferably less than 0.1wt%, preferably 0%. Preferably, the supported catalyst is completely free of metals other than copper, titanium and zirconium.

[0050] The fourth aspect of the present invention provides a method for preparing the above-mentioned supported catalyst, comprising the following steps: second impregnating the above-mentioned composite oxide support with a solution of a soluble salt of Cu, followed by second drying and second calcination.

[0051] According to some embodiments of the method for preparing a supported catalyst of the present invention, the molar ratio of the composite oxide support to the soluble salt of Cu is 1:0.03-0.6, for example, 1:0.03-0.4, 1:0.04-0.25, 1:0.05-0.32, 1:0.06-0.5. The moles of the composite oxide support are calculated based on Si, and the soluble salt of Cu is calculated based on the Cu element.

[0052] According to some embodiments of the method for preparing a supported catalyst of the present invention, the soluble salt of Cu is selected from at least one of copper chloride, copper sulfate, copper nitrate, copper acetate and disodium copper ethylenediaminetetraacetate (EDTA-Cu-15).

[0053] According to some embodiments of the method for preparing a supported catalyst of the present invention, the conditions for the second impregnation include: a temperature of 20 to 60° C. and a time of 0.5 to 8 hours.

[0054] According to some embodiments of the method for preparing a supported catalyst of the present invention, the second drying conditions include: a temperature of 105 to 180° C. and a time of 2 to 8 hours.

[0055] According to some embodiments of the method for preparing a supported catalyst of the present invention, the conditions for the second calcination include: a temperature of 450 to 650° C. and a time of 3 to 8 hours.

[0056] According to some embodiments of the method for preparing a supported catalyst according to the present invention, the amounts of the SiO2 microsphere carrier and the solution of the titanium compound are such that, based on the total weight of the prepared composite oxide carrier of SiO2 and TiO2 and / or ZrO2, the content of TiO2 and / or ZrO2 is 5 to 25 wt%, and the content of SiO2 is 75 to 95 wt%.

[0057] According to some embodiments of the method for preparing a supported catalyst of the present invention, the amount of the soluble salt of the second impregnation Cu of the composite oxide support of SiO2 and TiO2 and / or ZrO2 satisfies that the content of CuO in terms of CuO is 5-25wt% based on the total weight of the supported catalyst, such as but not limited to 5-20wt%, 5-15wt%, 5-10wt%, 10-25wt%, 10-20wt%, 10-15wt%, 12-25wt%, 12-20wt%, 12-15wt%, 15-25wt%, 15-20wt%, 20-25wt%, etc.

[0058] The fifth aspect of the present invention provides a catalyst composition, comprising a homogeneous catalyst and the above-mentioned supported catalyst.

[0059] According to some embodiments of the catalyst composition of the present invention, homogeneous catalysts commonly used in the art can be used, such as transition metal ruthenium carbene complexes, Grubbs catalysts (such as catalysts for olefin metathesis), triphenylphosphine and triphenylphosphine chlorides of platinum group metals. Preferably, the homogeneous catalyst includes triphenylphosphine and triphenylphosphine chlorides of platinum group metals.

[0060] Specifically, the transition metal ruthenium carbene complex catalyst includes but is not limited to the following structures of formula (1) to formula (7):

[0061]

[0062] The structure of the Grubbs catalyst includes but is not limited to that shown in formula (8):

[0063]

[0064] According to some embodiments of the hydrogenation method of hydrogenated nitrile rubber of the present invention, the triphenylphosphine chloride of a platinum group metal is triphenylphosphine rhodium chloride and / or triphenylphosphine ruthenium chloride.

[0065] According to some embodiments of the hydrogenation method of hydrogenated nitrile rubber of the present invention, the weight ratio of triphenylphosphine to triphenylphosphine chloride of platinum group metal is 2 to 5: 1. For example, but not limited to, 2 to 5: 1, 2 to 4: 1, 2 to 3: 1, etc.

[0066] According to some embodiments of the hydrogenation method of hydrogenated nitrile rubber of the present invention, the weight ratio of the supported catalyst to the homogeneous catalyst is 1:0.01-0.3, such as but not limited to 1:0.05-0.3, 1:0.1-0.3, 1:0.15-0.3, 1:0.16-0.3, etc.

[0067] The sixth aspect of the present invention provides a method for hydrogenating a polymer, comprising: dissolving the polymer in an organic solvent, then adding the above-mentioned catalyst composition, and reacting the polymer with hydrogen in the presence of the above-mentioned catalyst composition. The hydrogenation method is usually carried out in a reactor, first adding the polymer dissolved in an organic solvent into the reactor, then adding the catalyst composition, then closing the reactor, introducing hydrogen to replace air, and reacting the polymer with hydrogen in the presence of the catalyst composition.

[0068] According to some embodiments of the high molecular weight polymer hydrogenation method of the present invention, the amount of the supported catalyst is 5-20wt% of the high molecular weight polymer, such as 5-20wt%, 5-15wt%, 5-10wt%, 10-20wt%, 10-15wt%, 15-20wt%, etc.

[0069] According to some embodiments of the high molecular weight polymer hydrogenation method of the present invention, the reaction conditions include: temperature of 30 to 90° C., hydrogen pressure of 5 to 10 MPa, and time of 5 to 10 h.

[0070] According to some embodiments of the high molecular weight polymer hydrogenation method of the present invention, the amount of organic solvent used to dissolve the high molecular weight polymer is such that the content of the high molecular weight polymer in the organic solvent is 0.1 to 10 wt %. For example, 0.1-10wt%, 0.1-8wt%, 0.1-6wt%, 0.1-4wt%, 0.1-2wt%, 0.1-1wt%, 0.5-10wt%, 0.5-8wt%, 0.5-6wt%, 0.5-4wt%, 0.5-2wt%, 0.5-1wt%, 1-10wt%, 1-8wt%, 1-6wt%, 1-4wt%, 1-2wt%, 3-10wt%, 3-8wt%, 3-6wt%, 3-4wt%, 5-10wt%, 5-8wt%, 5-6wt%, 7-10wt%, 7-8wt%, 8-10wt%, 9-10wt% and the like, based on the total weight of the polymer and the solvent.

[0071] According to some embodiments of the hydrogenation method of the polymer of the present invention, the polymer is an unsaturated copolymer of a conjugated diene and a copolymerizable monomer. The conjugated diene is selected from at least one of butadiene, isoprene, piperylene and 2,3-dimethylbutadiene, preferably butadiene and / or isoprene, more preferably butadiene. The copolymerizable monomer is selected from at least one of acrylonitrile, methacrylonitrile, styrene, propyl acrylate, butyl acrylate, propyl methacrylate and butyl methacrylate, preferably acrylonitrile and / or methacrylonitrile, more preferably acrylonitrile.

[0072] According to some embodiments of the method for hydrogenating a high molecular weight polymer of the present invention, the high molecular weight polymer is nitrile rubber. In the art, nitrile rubber refers to a copolymer formed by polymerization of acrylonitrile and butadiene monomers.

[0073] According to some embodiments of the hydrogenation method of macromolecular polymer of the present invention, acrylonitrile-butadiene rubber is not particularly restricted, i.e. hydrogenation method of the present invention can be used for the hydrogenation of all acrylonitrile-butadiene rubbers. For example, acrylonitrile-butadiene rubber can be obtained by commercially available (for example from Rui Weng Co., Ltd. (such as grade DN series, 1000x132, 1001CG, 10001LG, 1031, 1041, 1041L, 1042, 1002, 1032J, 1022x59, 1052J, 1032-45, 1092-80, 1043, N917, 1094-80, 1014, 1034-60) or Qilu Petrochemical Co., Ltd.) or self-control.

[0074] For example, the acrylonitrile content of the nitrile rubber can be 15-55wt%, for example, 19-51wt%, 20-55wt%, 25-55wt%, 30-55wt%, 35-55wt%, 40-55wt%, 45-55wt%, 20-50wt%, 25-50wt%, 30-50wt%, 35-50wt%, 40-50wt%, 45-50wt%, 20- 45wt%, 25-45wt%, 30-45wt%, 35-45wt%, 40-45wt%, 20-40wt%, 25-40wt%, 30-40wt%, 35-40wt%, 20-35wt%, 25-35wt%, 30-35wt%, 20-25wt%, 20-30wt%, 25-30wt%, etc., including ranges between any two of the above values.

[0075] For example, the Mooney viscosity (ML, 100°C, 1+4) of the nitrile rubber can be 20-100, such as 20-40, 20-60, 20-80, 25-35, 25-55, 25-75, 25-95, 30-50, 30-70, 30-90, 35-45, 35-65, 35-85, 40-60, 40-80, 40-100, 45-55, 45-75, 45-95, 50-70, 50-90, 55-65, 55-85, 60-80, 60-100, 65-75, 65-95, 70-90, 75-85, 80-100, 85-95, 90-100, etc., including ranges between any two of the above values.

[0076] According to some embodiments of the high molecular weight polymer hydrogenation method of the present invention, the organic solvent is selected from at least one of chlorobenzene, acetone, butanone, tetrahydrofuran, dichloromethane, chloroform, cyclohexanone, ethyl acetate and dimethylformamide.

[0077] According to some embodiments of the polymer hydrogenation method of the present invention, the polymer hydrogenation method may further include: after the reaction is completed, recovering the supported catalyst by filtration or centrifugal separation, and recovering the homogeneous catalyst by ion exchange with an ion exchange resin.

[0078] According to some embodiments of the method for hydrogenating a high molecular weight polymer of the present invention, the degree of hydrogenation is at least 90%, for example but not limited to, at least 91%, at least 92%, at least 93%, at least 94%, at least 95%, at least 96%, at least 97%, at least 98%, at least 99%. The test method for the degree of hydrogenation is SH / T 1762-2008 / ISO 14558:2000.

[0079] According to some embodiments of the method for hydrogenating a high molecular weight polymer according to the present invention, the selectivity is at least 98%, for example but not limited to, at least 99%, at least 99.1%, at least 99.2%, at least 99.3%, at least 99.4%, at least 99.5%, at least 99.6%, at least 99.7%, at least 99.8%, at least 99.9%, 100%. The test method for the selectivity is to use infrared spectrum detection, and the instrument used is a Nicolet 560 Fourier transform infrared spectrometer produced by Nicolet Corporation of the United States.

[0080] The seventh aspect of the present invention provides a hydrogenated high molecular polymer obtained by the above hydrogenation method, preferably a hydrogenated nitrile rubber.

[0081] According to some embodiments of the hydrogenated high molecular polymer of the present invention, preferably hydrogenated nitrile rubber, the degree of hydrogenation of the hydrogenated high molecular polymer, preferably hydrogenated nitrile rubber is at least 90%, such as but not limited to at least 91%, at least 92%, at least 93%, at least 94%, at least 95%, at least 96%, at least 97%, at least 98%, at least 99%. The test method of the degree of hydrogenation is SH / T 1762-2008 / ISO 14558:2000.

[0082] According to some embodiments of the hydrogenated nitrile rubber of the present invention, the hydrogenated nitrile rubber has excellent characteristics such as good oil resistance, heat resistance, chemical corrosion resistance, odor resistance, high tear resistance and wear resistance.

[0083] The eighth aspect of the present invention provides the above-mentioned composite oxide carrier, the composite oxide carrier obtained by the above-mentioned composite oxide carrier preparation method, the above-mentioned loaded catalyst, the loaded catalyst obtained by the above-mentioned loaded catalyst preparation method, the above-mentioned catalyst composition, the hydrogenated polymer obtained by the above-mentioned polymer hydrogenation method or the above-mentioned hydrogenated polymer in rubber products or their manufacture, especially in the field of hydrogenated nitrile rubber products or their manufacture.

[0084] Beneficial effects of the present invention:

[0085] (1) Using an impregnation solution containing an organic cationic quaternary ammonium salt to modify the composite support of SiO2 and Group IVB metal oxide can significantly improve the dispersion of the active components on the catalyst surface and control the size of the active component Cu atomic cluster to be no larger than 5nm, thereby significantly improving the hydrogenation activity of the catalyst.

[0086] (2) The supported catalyst is prepared based on a composite carrier of SiO2 treated with organic cationic quaternary ammonium salt and Group IVB metal oxide. The pore structure is suitable for the hydrogenation of macromolecules such as nitrile rubber. The TiO2 and / or ZrO2 on the surface of the carrier can improve the hydrogenation activity of the catalyst. The catalyst has good hydrogenation activity and stability.

[0087] (3) The supported catalyst of the present invention is coordinated with a homogeneous catalyst to achieve hydrogenation saturation of the polymer material at a relatively low temperature and pressure, and the obtained hydrogenated polymer (such as hydrogenated nitrile rubber) product has a relatively high degree of hydrogenation.

[0088] (4) After the reaction is completed, the supported catalyst is recovered by filtration or centrifugal separation, and the homogeneous catalyst is recovered by ion exchange with an ion exchange resin, which can ensure that the supported catalyst can be reused multiple times and the catalyst can be easily separated and recovered.

[0089] (5) The supported catalyst and hydrogenation method of hydrogenated high molecular weight polymer (e.g., hydrogenated nitrile rubber) of the present invention use non-precious metals as active components to prepare supported catalysts for hydrogenation of nitrile rubber for the first time, thereby avoiding the problem of loss of precious metal active components, further improving the recyclability of the catalyst, and significantly reducing the cost of the catalyst, thereby reducing the production cost of the hydrogenated high molecular weight polymer (hydrogenated nitrile rubber). BRIEF DESCRIPTION OF THE DRAWINGS

[0090] Figure 1 This is the infrared spectrum of the composite oxide support of Example 1 of the present invention.

[0091] Figure 2 This is a TEM image of supported catalyst A of Example 13 of the present invention.

[0092] Figure 3 This is the infrared spectrum of the TiO2-SiO2 composite carrier of comparative example 1 that has not been surface treated.

[0093] Figure 4 This is the infrared spectrum of the surface-treated SiO2 carrier of test comparative example 5.

[0094] Figure 5 It is a comparison chart of infrared spectra of the carriers of Example 1, Test Comparative Example 1, and Test Comparative Example 5. DETAILED DESCRIPTION

[0095] In order to make the present invention more easily understood, the present invention will be described in detail below in conjunction with embodiments. These embodiments are only for illustration and are not intended to limit the application scope of the present invention.

[0096] In the following examples and comparative examples,

[0097] (1) SiO2 microsphere carrier was purchased from Shandong Bangkai Materials Co., Ltd.

[0098] (2) Dimethyldioctadecylammonium chloride, purchased from Beijing Bailingwei Technology Co., Ltd., CAS No. 61789-80-8.

[0099] (3) Hexadecyltrimethylammonium chloride, purchased from Beijing Bailingwei Technology Co., Ltd., CAS No. 112-02-7.

[0100] (4)C 12-14 -Alkyl dimethyl ethyl benzyl ammonium chloride was purchased from Beijing Bailingwei Technology Co., Ltd. with a CAS number of 85409-23-0.

[0101] (5) The content of Cu and its oxides, expressed as CuO, was analyzed using an Optima 8300 ICP atomic emission spectrometer (PE) according to standard JY / T 0567-2020.

[0102] (6) TiO2 content is measured using a spectrophotometer. The principle used is: in sulfuric acid solution, Ti 4+ It forms a yellow complex with hydrogen peroxide. Titanium dioxide forms titanium sulfate in hot sulfuric acid, and titanium sulfate reacts with hydrogen peroxide to form a stable orange-yellow [TiO(H2O2)] 2- , measured at 430 nm using a Unico UV-2100 spectrophotometer.

[0103] (7) Similarly, the ZrO2 content was determined using a spectrophotometer.

[0104] (8) Infrared spectra were measured using a Nicolet iS50 infrared spectrometer. Sample preparation and scanning were performed using the attenuated total reflection mode. The scanning range was 4000–400 cm -1 , resolution 4cm -1 , scan times 32 times.

[0105] (9) TEM characterization conditions: The catalyst was observed using a high-resolution transmission electron microscope (Jem-3010) with an acceleration voltage of 200 KV for HR-TEM characterization. The samples were fully ground into powder before testing. A small amount of the sample was added to anhydrous ethanol and placed in an ultrasonic cleaning machine (model PS-10, Shenzhen Jiekang Ultrasonic Cleaning Machine Co., Ltd.) for ultrasonic separation for 15 to 20 minutes. Finally, the suspension was continuously dripped onto the microgrid using a dropper and allowed to dry naturally.

[0106] (10) The particle size of the atomic cluster of the active component copper was characterized by transmission electron microscopy (TEM) and measured according to the scale.

[0107] [Example 1]

[0108] Take SiO2 microsphere carrier (particle size 20μm, average pore size 110nm, specific surface area 78m 2 / g) 85g, impregnated with 420mL of an aqueous solution of titanium sulfate with a concentration of 0.45mol / L, at 25°C for 6h, dried at 110°C for 6h, and calcined at 550°C for 5h. A TiO2-SiO2 composite carrier with a TiO2 content of 15wt% (SiO2 content of 85wt%) was obtained.

[0109] Take 5g of dimethyldioctadecylammonium chloride, add 95g of o-xylene, and mix evenly with 10mL of hydrochloric acid (mass fraction 37wt%) to prepare an impregnation solution. Use the above impregnation solution to impregnate the TiO2-SiO2 composite carrier at 20°C. After impregnation for 2h, dry it at 60°C for 12h to obtain a TiO2-SiO2 composite oxide carrier.

[0110] The prepared composite oxide support was characterized by infrared spectroscopy. Figure 1 As shown, the infrared spectrum of the SiO2-TiO2 composite oxide after surface treatment. It can be seen from the infrared spectrum that the surface characteristics of the composite oxide support of Example 1 are as follows: -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks at 620 cm -1 、649cm -1 、708cm -1There are characteristic peaks at 2850cm -1 、2919cm -1 、2955cm -1 There are characteristic peaks.

[0111] [Example 2]

[0112] The preparation method of the TiO2-SiO2 composite carrier is the same as that in Example 1, except that 420 mL of an aqueous solution of titanium sulfate with a concentration of 0.45 mol / L is replaced by 420 mL of a dilute sulfuric acid solution of titanic acid with a concentration of 0.86 mol / L to obtain a TiO2-SiO2 composite carrier with a TiO2 content of 25 wt% (SiO2 content of 75 wt%).

[0113] Take 4g of dimethyldioctadecylammonium chloride, add 96g of o-xylene, and mix evenly with 8mL of hydrochloric acid (mass fraction 37wt%) to prepare an impregnation solution. Use the above impregnation solution to impregnate the TiO2-SiO2 composite carrier at 20°C. After impregnation for 2h, dry it at 60°C for 12h to obtain a TiO2-SiO2 composite oxide carrier.

[0114] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks.

[0115] [Example 3]

[0116] The preparation method of the TiO2-SiO2 composite carrier is the same as that in Example 1, except that 420 mL of an aqueous solution of titanium sulfate with a concentration of 0.45 mol / L is replaced by 398 mL of an aqueous solution of titanium tetrachloride with a concentration of 0.38 mol / L to obtain a TiO2-SiO2 composite carrier with a TiO2 content of 12 wt% (SiO2 content of 88 wt%).

[0117] Take 3g of dimethyldioctadecylammonium chloride, add 97g of o-xylene, and mix evenly with 7mL of hydrochloric acid (mass fraction 37wt%) to prepare an impregnation solution. Use the above impregnation solution to impregnate the TiO2-SiO2 composite carrier at 20°C. After impregnation for 2h, dry it at 60°C for 12h to obtain a TiO2-SiO2 composite oxide carrier.

[0118] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks.

[0119] [Example 4]

[0120] The preparation method of the TiO2-SiO2 composite carrier is the same as that in Example 1, except that 420 mL of an aqueous solution of titanium sulfate with a concentration of 0.45 mol / L is replaced by 360 mL of an ethanol solution of tetrabutyl titanate with a concentration of 0.63 mol / L to obtain a TiO2-SiO2 composite carrier with a TiO2 content of 18 wt% (SiO2 content of 82 wt%).

[0121] Take 2g of dimethyldioctadecylammonium chloride, add 98g of o-xylene, and mix evenly with 5mL of hydrochloric acid (mass fraction 37wt%) to prepare an impregnation solution. Use the above impregnation solution to impregnate the TiO2-SiO2 composite carrier at 20°C. After impregnation for 2h, dry it at 60°C for 12h to obtain a TiO2-SiO2 composite oxide carrier.

[0122] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks.

[0123] [Example 5]

[0124] The preparation method of the TiO2-SiO2 composite carrier is the same as that in Example 1, except that 420 mL of an aqueous solution of titanium sulfate with a concentration of 0.45 mol / L is replaced by 123 mL of an ethanol solution of tetrabutyl titanate with a concentration of 0.51 mol / L to obtain a TiO2-SiO2 composite carrier with a TiO2 content of 5 wt% (SiO2 content is 95 wt%).

[0125] Take 1g of hexadecyltrimethylammonium chloride, add 99g of o-xylene, and mix evenly with 3mL of hydrochloric acid (mass fraction 37wt%) to prepare an impregnation solution. Use the above impregnation solution to impregnate the TiO2-SiO2 composite carrier at 20°C. After impregnation for 4h, dry it at 80°C for 12h to obtain a TiO2-SiO2 composite oxide carrier.

[0126] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2840-2970cm -1There are three characteristic peaks.

[0127] [Example 6]

[0128] The preparation method of the TiO2-SiO2 composite carrier is the same as that of Example 1, except that the calcination at 550°C for 5 hours is replaced by calcination at 650°C for 7 hours. A TiO2-SiO2 composite carrier with a TiO2 content of 15 wt% (SiO2 content of 85 wt%) is obtained.

[0129] Take 5g of C 12-14 -alkyl dimethyl ethyl benzyl ammonium chloride, add 95g of o-xylene, and evenly mix with 10mL of hydrochloric acid (mass fraction 37wt%) to prepare an impregnation solution. Use the above impregnation solution to impregnate the TiO2-SiO2 composite carrier at 40°C. After impregnation for 2h, dry it at 100°C for 12h to obtain a TiO2-SiO2 composite oxide carrier.

[0130] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks.

[0131] [Example 7]

[0132] The method of Example 1 was followed, except that the aqueous solution of titanium sulfate was replaced with 420 mL of an aqueous solution of zirconium tetrachloride having a concentration of 0.29 mol / L, to finally obtain a ZrO2-SiO2 composite carrier. A ZrO2-SiO2 composite carrier having a ZrO2 content of 15 wt% (SiO2 content of 85 wt%) was obtained.

[0133] Take 5g of dimethyldioctadecylammonium chloride, add 95g of o-xylene, and mix evenly with 10mL of hydrochloric acid (mass fraction 37wt%) to prepare an impregnation solution. Use the above impregnation solution to impregnate the ZrO2-SiO2 composite carrier at 20°C. After impregnation for 2h, dry it at 60°C for 12h to obtain a ZrO2-SiO2 composite oxide carrier.

[0134] The infrared spectrum of the obtained ZrO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1. The surface characteristics are as follows: -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks.

[0135] [Example 8]

[0136] Take 85g of SiO2 microsphere carrier, impregnate 280mL of titanium sulfate aqueous solution with a concentration of 0.45mol / L, immerse for 6h at 25℃, dry the precipitate at 110℃ for 6h, and calcine at 550℃ for 5h. Then impregnate 300mL of zirconium nitrate aqueous solution with a concentration of 0.14mol / L, immerse for 4h at 25℃, dry the precipitate at 110℃ for 8h, and calcine at 550℃ for 6h.

[0137] A TiO2-ZrO2-SiO2 composite carrier (SiO2 content is 85wt%) with a TiO2 content of 10wt% and a ZrO2 content of 5wt% was obtained.

[0138] Take 5g of dimethyldioctadecylammonium chloride, add 95g of o-xylene, and mix evenly with 10mL of hydrochloric acid (mass fraction 37wt%) to prepare an impregnation solution. Use the above impregnation solution to impregnate the TiO2-ZrO2-SiO2 composite carrier at 20°C. After impregnation for 2h, dry it at 60°C for 12h to obtain a TiO2-ZrO2-SiO2 composite oxide carrier.

[0139] The infrared spectrum of the obtained TiO2-ZrO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks.

[0140] [Example 9]

[0141] The preparation method of the TiO2-SiO2 composite oxide carrier is the same as that of Example 1, except that the SiO2 microsphere carrier is replaced with a carrier having a particle size of 10 μm, an average pore size of 200 nm, and a specific surface area of ​​60 m 2 / g SiO2 microsphere carrier.

[0142] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks.

[0143] [Example 10]

[0144] The preparation method of the TiO2-SiO2 composite oxide carrier is the same as that of Example 1, except that the SiO2 microsphere carrier is replaced with a carrier having a particle size of 5 μm, an average pore size of 120 nm, and a specific surface area of ​​75 m 2 / g SiO2 microsphere carrier.

[0145] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks.

[0146] [Example 11]

[0147] The preparation method of the TiO2-SiO2 composite oxide carrier is the same as that of Example 1, except that the SiO2 microsphere carrier is replaced with a carrier having a particle size of 30 μm, an average pore size of 1000 nm, and a specific surface area of ​​37 m 2 / g SiO2 microsphere carrier.

[0148] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks.

[0149] [Example 12]

[0150] The preparation method of the TiO2-SiO2 composite oxide carrier is the same as that of Example 1, except that the solvent in the impregnation solution is replaced by pyridine instead of o-xylene.

[0151] The infrared spectrum of the obtained TiO2-SiO2 composite oxide support is similar to that of the composite oxide support in Example 1, and the surface characteristics are as follows: -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks.

[0152] [Example 13]

[0153] 100 g of the composite oxide supports prepared in Examples 1 to 12 were respectively put into 500 mL of an aqueous solution of copper nitrate having a Cu content (in terms of CuO) of 5.26 to 33.33 g, immersed at 25° C. for 180 minutes, dried at 110° C. for 6 hours, and then calcined at 500° C. for 4 hours to obtain Cu / TiO2-SiO2 catalysts (supported catalysts AI, L, M, N, O) having a Cu content of 5 to 25 wt% of Cu and its oxide in terms of CuO. The details are shown in Table 1.

[0154] The prepared supported catalyst A was subjected to TEM characterization. Figure 2 ,Depend on Figure 2It can be seen that the active components are evenly dispersed, the atomic cluster particle size of the active components is 2 to 5 nm, and the average particle size is 3.3 nm.

[0155] [Example 13]

[0156] 100 g of the composite oxide support prepared in Example 1 was respectively put into 500 mL of an aqueous solution of copper nitrate containing 32 g of Cu, immersed at 20° C. for 180 minutes, dried at 110° C. for 6 hours, and then calcined at 600° C. for 6 hours to obtain a Cu / TiO2-SiO2 catalyst (supported catalyst J) having a Cu and its oxide content of 24 wt% in terms of CuO. The details are shown in Table 1.

[0157] [Example 14]

[0158] 100 g of the composite oxide support prepared in Example 1 was respectively put into 500 mL of an aqueous solution of copper nitrate containing 32 g of Cu, immersed at 30° C. for 180 minutes, dried at 110° C. for 6 hours, and then calcined at 650° C. for 7 hours to obtain a Cu / TiO2-SiO2 catalyst (supported catalyst K) having a Cu and its oxide content of 24 wt% in terms of CuO. The details are shown in Table 1.

[0159] Table 1

[0160]

[0161]

[0162] The particle size, average pore size, and specific surface area of ​​the supported catalyst AN were tested, and the results are shown in Table 2.

[0163] The average particle size was measured according to the NB / SH / T 0951-2017 test method using a laser particle size analyzer model MS2000 produced by Malvern.

[0164] The average pore size and specific surface area are determined according to the first part of the mercury intrusion method for determining the pore size distribution and porosity of solid materials by the mercury intrusion method and gas adsorption method in GBT 21650.1-2008, using a high-performance fully automatic mercury intrusion instrument of the AutoPoreIV 9500 model from Micromeritics Instruments, USA.

[0165] Table 2

[0166] Supported catalyst number Particle size, μm Average pore size, nm <![CDATA[Specific surface area, m 2 / g]]> A 20 102 47 B 10 100 51 C 5 104 55 D 20 103 54 E 20 102 65 F 22 106 52 G 20 102 55 H 20 103 54 I 20 100 51 J 20 104 51 K 20 104 52 L 10 186 41 M 5 107 46 N 30 983 36

[0167] [Test Example 1]

[0168] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of supported catalyst A, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.0g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 6MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0169] The obtained hydrogenated nitrile rubber was tested for its degree of hydrogenation using the test method of SH / T 1762-2008 / ISO 14558:2000 (measurement of unsaturation), and the result showed that the degree of hydrogenation was 95.2%.

[0170] The obtained hydrogenated nitrile rubber was tested for selectivity by infrared spectrum detection. The instrument used was Nicolet 560 Fourier transform infrared spectrometer produced by Nicolet Company of the United States. It was detected that the absorption peak intensity of -CN in the spectrum did not weaken after hydrogenation, and no absorption peak representing -NH2 appeared, indicating that -CN did not change before and after the reaction, that is, -CN was not hydrogenated, and the selectivity was 100%. The result showed that the selectivity was 100%.

[0171] [Test Example 2]

[0172] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of supported catalyst A, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.0g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, and reaction time 6h; hydrogenated nitrile rubber is obtained.

[0173] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 96.1% and the selectivity was 100%.

[0174] [Test Example 3]

[0175] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of supported catalyst B, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.0g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, and reaction time 6h; hydrogenated nitrile rubber is obtained.

[0176] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1, and the results showed that the hydrogenation degree was 93.8% and the selectivity was 100%.

[0177] [Test Example 4]

[0178] Take 2L of 3wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of supported catalyst C, 0.5g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.2g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, and reaction time 6h; hydrogenated nitrile rubber is obtained.

[0179] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1, and the results showed that the hydrogenation degree was 97.1% and the selectivity was 100%.

[0180] [Test Example 5]

[0181] Take 2L of 3wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of supported catalyst A, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.0g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, and reaction time 6h; hydrogenated nitrile rubber is obtained.

[0182] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1, and the results showed that the hydrogenation degree was 97.6% and the selectivity was 100%.

[0183] [Test Example 6]

[0184] After the reaction of Test Example 5, the supported catalyst A was centrifuged and recovered, stirred and washed in an organic solvent chlorobenzene for 4 hours, and centrifuged. The same reaction conditions as Test Example 5 were adopted, and it was added to the reaction system again to investigate its NBR hydrogenation catalytic performance. The experiment was repeated 4 times, and the results of hydrogenation degree (tested according to the method of Test Example 1) and selectivity (NMR determination: compared with the CN group content in the raw material and the hydrogenation product) are listed in Table 3.

[0185] Table 3

[0186] Reuse 1 time Reuse 2 times Reuse 3 times Reuse 4 times Degree of hydrogenation 94.5% 93.6% 93.3% 92.8% Selectivity 100% 100% 100% 100%

[0187]

Test Example 7

[0188] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of supported catalyst D, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.0g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, and reaction time 6h; hydrogenated nitrile rubber is obtained.

[0189] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1, and the results showed that the hydrogenation degree was 97.6% and the selectivity was 100%.

[0190]

Test Example 8

[0191] The method of Test Example 1 was followed, except that the supported catalyst A was replaced by supported catalyst E, and hydrogenated nitrile rubber was finally obtained.

[0192] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 91.2% and the selectivity was 100%.

[0193] [Test Example 9]

[0194] The method of Test Example 1 is followed, except that the supported catalyst A is replaced by supported catalyst F, to finally obtain hydrogenated nitrile rubber.

[0195] The hydrogenation degree of the obtained hydrogenated nitrile rubber was tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 94.1% and the selectivity was 100%.

[0196] [Test Example 10]

[0197] The method of Test Example 1 is followed, except that the supported catalyst A is replaced by supported catalyst G, to finally obtain hydrogenated nitrile rubber.

[0198] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.1% and the selectivity was 100%.

[0199] [Test Example 11]

[0200] The method of Test Example 1 is followed, except that the supported catalyst A is replaced by supported catalyst H, to finally obtain hydrogenated nitrile rubber.

[0201] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.8% and the selectivity was 100%.

[0202] [Test Example 12]

[0203] The method of Test Example 1 is followed, except that the supported catalyst A is replaced by supported catalyst I, and finally hydrogenated nitrile rubber is obtained.

[0204] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.4% and the selectivity was 100%.

[0205] [Test Example 13]

[0206] The method of Test Example 1 was followed, except that supported catalyst A was replaced by supported catalyst J, and hydrogenated nitrile rubber was finally obtained.

[0207] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.7% and the selectivity was 100%.

[0208] [Test Example 14]

[0209] The method of Test Example 1 is followed, except that the supported catalyst A is replaced by supported catalyst K, and finally hydrogenated nitrile rubber is obtained.

[0210] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 94.8% and the selectivity was 100%.

[0211] [Test Example 15]

[0212] The method of Test Example 1 was followed, except that the supported catalyst A was replaced by supported catalyst L, and hydrogenated nitrile rubber was finally obtained.

[0213] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.3% and the selectivity was 100%.

[0214] [Test Example 16]

[0215] The method of Test Example 1 is followed, except that the supported catalyst A is replaced by supported catalyst M, and finally hydrogenated nitrile rubber is obtained.

[0216] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.0% and the selectivity was 100%.

[0217] [Test Example 17]

[0218] The method of Test Example 1 is followed, except that the supported catalyst A is replaced by supported catalyst N, to finally obtain hydrogenated nitrile rubber.

[0219] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 96.1% and the selectivity was 100%.

[0220] [Test Example 18]

[0221] The method of Test Example 1 was followed, except that the reaction conditions were: temperature 80° C., hydrogen pressure 6 MPa, and reaction time 8 h.

[0222] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 93.9% and the selectivity was 100%.

[0223] [Test Example 19]

[0224] The method of Test Example 1 was followed, except that the reaction conditions were: temperature 70° C., hydrogen pressure 6 MPa, and reaction time 8 h.

[0225] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 91.7% and the selectivity was 100%.

[0226] [Test Example 20]

[0227] The method of Test Example 1 was followed, except that the reaction conditions were: temperature 60° C., hydrogen pressure 6 MPa, and reaction time 8 h.

[0228] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 90.2% and the selectivity was 100%.

[0229] [Test Example 21]

[0230] The method of Test Example 1 was followed, except that the reaction conditions were: temperature 50° C., hydrogen pressure 6 MPa, and reaction time 8 h.

[0231] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 88.2% and the selectivity was 100%.

[0232] [Test Example 22]

[0233] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of supported catalyst A, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.2g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 6MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0234] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.3% and the selectivity was 100%.

[0235] [Test Example 23]

[0236] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of supported catalyst A, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.6g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 6MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0237] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.4% and the selectivity was 100%.

[0238]

Test Example 24

[0239] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of supported catalyst A, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 2g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 6MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0240] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.3% and the selectivity was 100%.

[0241] [Test Example 25]

[0242] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 12g of supported catalyst A, 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.6g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 6MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0243] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 98.9% and the selectivity was 100%.

[0244] [Test Example 26]

[0245] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of supported catalyst A, 0.08g of homogeneous catalyst triphenylphosphine rhodium chloride, and 0.32g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 95°C, hydrogen pressure 8MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0246] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 91.3% and the selectivity was 100%.

[0247] [Test Example 27]

[0248] Take 2L of 4wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 8g of supported catalyst A, 0.7g of homogeneous catalyst triphenylphosphine ruthenium chloride, and 1.5g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 6MPa, and reaction time 8h; hydrogenated nitrile rubber is obtained.

[0249] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.2% and the selectivity was 100%.

[0250]

Test Example 28

[0251] The method of Test Example 1 is followed, except that the supported catalyst A is replaced by supported catalyst O, to finally obtain hydrogenated nitrile rubber.

[0252] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 95.7% and the selectivity was 100%.

[0253] [Comparative Test Example 1]

[0254] The TiO2-SiO2 composite oxide carrier without surface treatment in Example 1 was used, and the infrared spectrum was as follows: Figure 3 As shown, that is, the infrared spectrum of the TiO2-SiO2 composite carrier without surface treatment.

[0255] Then, the active components were loaded according to the method of Example 12, and finally a Cu / TiO2-SiO2 catalyst with a Cu content of 24 wt% was prepared. The particle size of the Cu atomic cluster was 20-50 nm.

[0256] According to the method of Test Example 1, hydrogenated nitrile rubber was finally obtained.

[0257] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1, and the results showed that the hydrogenation degree was 88.2% and the selectivity was 99%.

[0258] [Test Comparative Example 2]

[0259] The TiO2-SiO2 composite oxide carrier of Example 1 was used and the method of Example 5 was followed, except that the copper nitrate solution was replaced by a nickel nitrate solution, to finally prepare a Ni / ZrO2-SiO2 catalyst (supported catalyst DB1) with a Ni content of 24 wt%. The particle size of the Ni atomic cluster was 10 to 30 nm.

[0260] The method of Test Example 1 was followed, except that the supported catalyst A was replaced by supported catalyst DB1, and finally hydrogenated nitrile rubber was obtained.

[0261] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1, and the results showed that the hydrogenation degree was 78% and the selectivity was 82.5%.

[0262] [Test comparison example 3]

[0263] The method of Test Example 1 is followed, except that only supported catalyst A is used, as follows:

[0264] Take 2L of 3wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), add 9.4g of supported catalyst A, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, reaction time 6h; hydrogenated nitrile rubber is obtained.

[0265] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1. The results showed that the hydrogenation degree was 57.6% and the selectivity was 100%.

[0266] [Test comparison example 4]

[0267] The method of Test Example 5 is followed, except that only a homogeneous catalyst is used, as follows:

[0268] Take 2L of 3wt% NBR chlorobenzene solution (chlorobenzene is used to dissolve nitrile rubber), 0.4g of homogeneous catalyst triphenylphosphine rhodium chloride, and 1.0g of triphenylphosphine, and carry out catalyst hydrogenation reaction in a high-pressure reactor to obtain a rubber solution. The reaction conditions are: temperature 90°C, hydrogen pressure 8MPa, and reaction time 6h; hydrogenated nitrile rubber is obtained.

[0269] The hydrogenation degree and selectivity of the obtained hydrogenated nitrile rubber were tested according to the method of Test Example 1, and the results showed that the hydrogenation degree was 67.2% and the selectivity was 100%.

[0270] [Test comparison example 5]

[0271] Take 85 g of SiO2 microsphere carrier (particle size: 20 μm, average pore size: 110 nm).

[0272] Take 5g of dimethyldioctadecylammonium chloride, add 95g of o-xylene, and mix evenly with 10mL of hydrochloric acid (mass fraction 37wt%) to prepare an impregnation solution. Use the above impregnation solution to impregnate the SiO2 microsphere carrier at 20°C. After impregnation for 2h, dry it at 60°C for 12h.

[0273] The infrared spectrum of the SiO2 carrier after surface treatment is shown in Figure 4 shown.

[0274] pass Figure 1 , Figures 3 to 5 It can be seen that the surface of the composite oxide support is treated with an impregnation solution containing an organic cationic quaternary ammonium salt, and the surface characteristics of the surface-treated composite oxide support are as follows: -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks at 610-720cm. The infrared spectrum of the TiO2-SiO2 composite oxide carrier without surface treatment and the infrared spectrum of the SiO2 carrier with surface treatment are -1 There are no three characteristic peaks at 2840-2970cm -1 The composite oxide carrier of the present invention can significantly improve the dispersion of active components on the catalyst surface, control the atomic clusters of active components to be no larger than 5 nm, and thus significantly improve the hydrogenation activity of the catalyst.

[0275] It can be seen from Test Examples 1-27 and Comparative Test Examples 1-4 that the present invention adopts a method of coordinating with a homogeneous catalyst to hydrogenate and saturate the polymer material at a relatively low temperature and pressure. The obtained hydrogenated nitrile rubber product has a relatively high degree of hydrogenation and can also ensure the multiple use of the supported catalyst and the easy separation and recovery of the catalyst.

[0276] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this field, under the technical enlightenment provided by the present invention, as common knowledge in the field, other equivalent variations and improvements can also be made, which should also be regarded as the protection scope of the present invention.

Claims

1. A composite oxide carrier, characterized in that: include: SiO2 and Group IVB metal oxide, wherein the Group IVB metal oxide is TiO2 and / or ZrO2, and the surface characteristics of the composite oxide carrier are infrared spectrum at 610-720cm -1 There are three characteristic peaks at 2840-2970cm -1 There are three characteristic peaks.

2. The composite oxide support according to claim 1, characterized in that The surface characteristics of the composite oxide support are as follows: the infrared spectrum is 620±1cm -1 、649±1cm -1 、708±1cm -1 There is a characteristic peak at 2850±1cm; and / or, the surface characteristic of the composite oxide support is that the infrared spectrum is -1 、2919±1cm -1 、2955±1cm -1 There are characteristic peaks.

3. The composite oxide support according to claim 1, characterized in that The composite oxide carrier is obtained by surface treating a composite oxide carrier precursor of SiO2 and a Group IVB metal oxide with an impregnation solution containing an organic cationic quaternary ammonium salt. Preferably, the surface treatment is impregnation and drying. Preferably, the organic cationic quaternary ammonium salt is a C6 or higher long-chain alkyl quaternary ammonium salt, more preferably a C6 or higher long-chain alkyl halogen quaternary ammonium salt, more preferably selected from dimethyl dioctadecyl ammonium chloride, hexadecyl trimethyl ammonium chloride and C 12-14 -At least one of alkyl dimethyl ethyl benzyl ammonium chloride.

4. The composite oxide support according to any one of claims 1 to 3, characterized in that Based on the total weight of the composite oxide carrier, the content of the Group IVB metal oxide is 5 to 25 wt%, and the content of SiO2 is 75 to 95 wt%. Preferably, the content of the Group IVB metal oxide is 10 to 25 wt%, and the content of SiO2 is 75 to 90 wt%; and / or, the particle size of the composite oxide carrier is 5 to 30 μm; and / or, the average pore size is 100 to 1200 nm; and / or, the specific surface area is 30 to 200 m 2 / g.

5. A method for preparing a composite oxide support according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) first impregnating a SiO2 microsphere carrier with a solution containing a Group IVB metal compound, then first drying and first calcining to obtain a composite oxide carrier precursor, wherein the Group IVB metal compound is a titanium-containing compound and / or a zirconium-containing compound; (2) The composite oxide support precursor is surface treated with an impregnation solution containing an organic cationic quaternary ammonium salt to obtain the composite oxide support.

6. The preparation method according to claim 5, characterized in that: The impregnation solution containing the organic cationic quaternary ammonium salt comprises the organic cationic quaternary ammonium salt, a solvent, and an acid; Preferably, in the impregnation solution containing the organic cationic quaternary ammonium salt, the concentration of the quaternary ammonium salt solution is 0.1-10 wt %.

7. The preparation method according to claim 6, characterized in that: The organic cationic quaternary ammonium salt is a C6 or higher long-chain alkyl quaternary ammonium salt, more preferably a C6 or higher long-chain alkyl halogen quaternary ammonium salt, more preferably selected from dimethyl dioctadecyl ammonium chloride, hexadecyl trimethyl ammonium chloride and C6 12-14 - at least one of alkyl dimethyl ethyl benzyl ammonium chloride; and / or The solvent is selected from at least one of deionized water, methanol, ethanol, acetone, butanone, tetrahydrofuran, o-xylene, p-xylene and pyridine, preferably selected from at least one of o-xylene, p-xylene and pyridine, more preferably o-xylene or pyridine; and / or The acid is selected from at least one of hydrochloric acid, sulfuric acid, nitric acid and citric acid, preferably hydrochloric acid.

8. The preparation method according to any one of claims 5 to 7, characterized in that: The surface treatment is immersion and drying. Preferably, the immersion conditions include: temperature of 20-60° C., time of 0.5-8 h; the drying conditions include: temperature of 50-120° C., time of 2-10 h.

9. The preparation method according to any one of claims 5 to 8, characterized in that: The SiO2 microsphere carrier has a particle size of 5 to 30 μm; and / or an average pore size of 100 to 1200 nm; and / or a specific surface area of ​​30 to 200 m 2 / g.

10. The preparation method according to any one of claims 5 to 9, characterized in that: The titanium-containing compound is selected from at least one of titanium sulfate, metatitanic acid, titanium tetrachloride and tetrabutyl titanate; and / or, the zirconium-containing compound is at least one selected from zirconium tetrachloride, zirconium sulfate, zirconium nitrate, zirconium oxychloride and zirconium oxalate; And / or, in the solution containing the titanium compound and / or the zirconium compound, the concentration of the titanium compound and / or the zirconium compound is 0.1 to 1.0 mol / L.

11. The preparation method according to any one of claims 5 to 10, characterized in that: The molar ratio of the SiO2 microsphere carrier to the IVB group metal compound is 3 to 40:1; and / or, the first impregnation conditions include: a temperature of 20 to 60°C and a time of 0.5 to 8 hours; and / or, the first drying conditions include: a temperature of 105 to 130°C and a time of 2 to 8 hours; and / or, the first calcination conditions include: a temperature of 450 to 650°C and a time of 3 to 8 hours.

12. A supported catalyst comprising: The composite oxide carrier according to any one of claims 1 to 4, and the active component Cu and its oxide supported on the carrier; the atomic cluster particle size of the active component copper is not greater than 5 nm; the content of Cu and its oxide calculated as CuO is 5 to 25 wt% based on the total weight of the supported catalyst.

13. The supported catalyst according to claim 12, characterized in that The supported catalyst has a particle size of 5 to 30 μm; and / or an average pore size of 100 to 1200 nm; and / or a specific surface area of ​​30 to 200 m 2 / g; and / or, the atomic cluster particle size of the active component copper is 2 to 5 nm.

14. A method for preparing a supported catalyst according to claim 12 or 13, comprising the following steps: The composite oxide support according to any one of claims 1 to 4 or the composite oxide support obtained by the preparation method according to any one of claims 5 to 9 is secondly impregnated with a solution of a soluble salt of Cu, and then second dried and second calcined.

15. The preparation method according to claim 14, characterized in that: The molar ratio of the composite oxide support to the soluble salt of Cu is 1:0.03-0.6; and / or, the conditions for the second impregnation include: a temperature of 20-60°C and a time of 0.5-8h; and / or, the conditions for the second drying include: a temperature of 105-180°C and a time of 2-8h; and / or, the conditions for the second calcination include: a temperature of 450-650°C and a time of 3-8h.

16. The preparation method according to claim 14 or 15, characterized in that: The soluble salt of Cu is selected from at least one of copper chloride, copper sulfate, copper nitrate, copper acetate and disodium copper ethylenediaminetetraacetate.

17. A catalyst composition comprising a homogeneous catalyst and the supported catalyst according to claim 12 or 13.

18. The catalyst composition according to claim 17, characterized in that The homogeneous catalyst includes triphenylphosphine and triphenylphosphine chloride of a platinum group metal; Preferably, the triphenylphosphine chloride of the platinum group metal is triphenylphosphine rhodium chloride and / or triphenylphosphine ruthenium chloride; Preferably, the weight ratio of triphenylphosphine to triphenylphosphine chloride of a platinum group metal is 2 to 5:

1.

19. The catalyst composition according to claim 17 or 18, characterized in that The weight ratio of the supported catalyst to the homogeneous catalyst is 1:0.01-0.

3.

20. A method for hydrogenating a high molecular weight polymer, comprising: An organic solvent is used to dissolve the high molecular polymer, and then the catalyst composition according to any one of claims 17 to 19 is added to react the high molecular polymer with hydrogen in the presence of the catalyst composition.

21. The hydrogenation method according to claim 20, characterized in that: The amount of the supported catalyst is 5-20 wt% of the polymer.

22. The hydrogenation method according to claim 20, characterized in that The reaction conditions include: temperature of 30-90° C., hydrogen pressure of 5-10 MPa, and reaction time of 5-10 h.

23. The hydrogenation method according to any one of claims 20 to 22, characterized in that: The high molecular polymer is nitrile rubber.

24. The hydrogenation method according to any one of claims 20 to 23, characterized in that: The organic solvent is selected from at least one of chlorobenzene, acetone, butanone, tetrahydrofuran, dichloromethane, chloroform, cyclohexanone, ethyl acetate and dimethylformamide.

25. The hydrogenated high molecular polymer obtained by the hydrogenation method according to any one of claims 20 to 24, preferably, the hydrogenated high molecular polymer is hydrogenated nitrile rubber.

26. Use of the composite oxide carrier according to any one of claims 1 to 4, the composite oxide carrier obtained by the preparation method according to any one of claims 5 to 11, the supported catalyst according to claim 12 or 13, the supported catalyst obtained by the preparation method according to any one of claims 14 to 16, the catalyst composition according to any one of claims 17 to 19, the hydrogenated polymer obtained by the polymer hydrogenation method according to any one of claims 20 to 24, or the hydrogenated polymer according to claim 25 in rubber products or their manufacture, especially in the field of hydrogenated nitrile rubber products or their manufacture.

Citation Information

Patent Citations

  • ZrO2-SiO2 compound oxides, its preparation method and application

    CN101007268A

  • Hydrogenation catalysts carrier with nickel and cobalt, hydro-catalyst and its preparing method

    CN101157056A

  • Preparation method of titanium-silicon material

    CN101683986A

  • Hydrogenation catalyst, preparation method and application thereof as well as hydrofining method

    CN102451721A

  • Hydrogenated butadiene-acrylonitrile rubber preparation method

    CN104140479A